Pengaruh Sektor Pertanian, Komoditas Produksi Dan Harga Jual Kopi Terhadap Pendapatan Asli Daerah - Iftihanah, Lilis Hidayatul (Independent: Journal of Economics, 2024)
The agricultural sector is a strategic sector and plays an important role in the national economy and the survival of the community. One form of domestic agriculture which is the main commodity, especially in the Suoh Region, is coffee plantations which have succeeded in becoming the largest contributor to domestic coffee production. This study aims to analyze the effect of the agricultural sector, production commodities and selling prices on the original income of the Suoh Region of Lampung Province for the 2018-2022 period. The type of research used is quantitative research with the analysis technique used, namely multiple linear regression analysis using SPSS version 20. The results of the analysis show that the agricultural sector, production commodities and selling prices have a partial and simultaneous effect on revenue. Because of that, all hypotheses in this study are accepted